Roots of Inequality - Oded Galor; Marc Klemp; Daniel C. Wainstock (Center for Economic Studies and ifo Institute (CESifo), 2023)
Why does inequality vary across societies? We advance the hypothesis that in a market economy, where earning differentials reflect variations in productive traits, a significant component of the differences in income inequality across societies can be attributed to variation in societal interpersonal diversity, shaped during the prehistoric Out-of-Africa Migration. The roots of income inequality within the US population provide supporting evidence for the hypothesis. It suggests that variation in income inequality across groups of individuals originating from different ancestral backgrounds can be traced to the degree of diversity of their ancestral populations as was carved in the course of the dispersal of humanity from Africa.
Keywords: D60; O10; Z10; 330; inequality; diversity; culture; out-of-Africa migration